Notochordal Cell-Based Treatment Strategies and Their Potential in Intervertebral Disc Regeneration - Bach, Frances C.; Poramba-Liyanage, Deepani W.; Riemers, Frank M.; Guicheux, Jerome; Camus, Anne; Iatridis, James C.; Chan, Danny; Ito, Keita; Le Maitre, Christine L.; Tryfonidou, Marianna A. (Frontiers in Cell and Developmental Biology, 2022)
Chronic low back pain is the number one cause of years lived with disability. In about 40% of patients, chronic lower back pain is related to intervertebral disc (IVD) degeneration. The standard-of-care focuses on symptomatic relief, while surgery is the last resort. Emerging therapeutic strategies target the underlying cause of IVD degeneration and increasingly focus on the relatively overlooked notochordal cells (NCs). NCs are derived from the notochord and once the notochord regresses they remain in the core of the developing IVD, the nucleus pulposus. The large vacuolated NCs rapidly decline after birth and are replaced by the smaller nucleus pulposus cells with maturation, ageing, and degeneration. Here, we provide an update on the journey of NCs and discuss the cell markers and tools that can be used to study their fate and regenerative capacity. We review the therapeutic potential of NCs for the treatment of IVD-related lower back pain and outline important future directions in this area. Promising studies indicate that NCs and their secretome exerts regenerative effects, via increased proliferation, extracellular matrix production, and anti-inflammatory effects. Reports on NC-like cells derived from embryonic- or induced pluripotent-stem cells claim to have successfully generated NC-like cells but did not compare them with native NCs for phenotypic markers or in terms of their regenerative capacity. Altogether, this is an emerging and active field of research with exciting possibilities. NC-based studies demonstrate that cues from developmental biology can pave the path for future clinical therapies focused on regenerating the diseased IVD.